PRESENCE D’EMPREINTES DE PAS DE DINOSAURIENS DANS LE CRETACE AU NORD D’EL BAYADH (Djebel Amour, Algérie) (Sciences & Technologie. B, Sciences de l'ingénieur, 2005)
In the northern part of El Bayadh, localised about 3 km from this town, many prints of dinosaurians steeps are present in the lower age of cretaceous (Valanginien). The prints were highlighted spread out over 1 km2 on the lumachellic clay-limestone pavement, and being distributed on two sites, site 1and site 2, that are approximately distant each other from 500 m. In sight ofstate in advanced works, at look paleontological excavations progress, only site1 was studied in this note. The ichnofossil analysis of the tracks reveals the presence, in-situ, of three ichnotypes. These lattest prints are presented in the form of two tridactyl bipeds and griffus having two different sizes and the third quadruped was shaped in rounded prints, like half-moon. The detailed biometric and systematic studies, in progress, will make it possible to specify their paleoichnologic appearance. The preliminary data allowed to assign that the whole of these tracks at two dinosaurians forms, where represented by two Théropodes carnivores and herbivorous Sauropode.